Interpretation Content of the Modern Musical Theater: Portrait in the Style of ad Libitum: ДО 195-РІЧЧЯ ДРАМИ «БОРИС ГОДУНОВ» ОЛЕКСАНДРА ПУШКІНА І 150-РІЧЧЯ ТРАГЕДІЇ «ЦАР БОРИС» ОЛЕКСІЯ ТОЛСТОГО - Solomonova, Olga (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2021)
Relevance of the study. The interpretive space of modern musical theater is one of the most dynamic, multivariate and modernized world culture phenomena. In the era of culture “non-classical paradigm” the past cult operas viability is maintained through their renewed representation and “alienation”. The refusal to perceive the author’s work as complete and the only possible for realization emancipates the modern interpretive strategy and opens up endless possibilities until the emergence of the “corporate” opera text’s phenomenon. So the interpretation process extends to the work’s “inner sanctum” — to its music and thus allows the involvement of the modern artist’s personality to co-author with the composer of the past. The unique example is the opera project “Boris” by corporate authorship of Modest Mussorgsky and contemporary Russian-German composer Sergei Nevsky (2020, Staatsoper). The need for update the ideas about the modern musical theater’s interpretive strategy and the lack of this project research provides the relevance and the innovative essence of the material. Main objective of the study is to determine the modern interpretive strategies of modern opera theater on the example of the project “Boris”. Methodology. The material specificity led to the adaptation of the fellowing research methods: the interpretive — to identify the modern musical theater main interpretive strategies in relation to the production of “Boris Godunov” by M. Mussorgsky with an emphasis on the project “Boris”; the hermeneutic-semantic — for the purpose of reveal the intonation-image specificity of the analyzed S. Nevsky’s project; the comparative — for juxtaposition of two co-operas authored by Mussorgsky and Nevsky as components of the project “Boris”; the holistic intonation analysis — to study the intonation and drama specifics of the hybrid work. Results and conclusions. The modernity interpretive reality initiates the emergence of radically new trends in the opera interpretation. An example of the modern musical theater innovative strategy is the hybrid project “Boris” synthesized from two stylistically contrasting operas that belong to different epochs: “Boris Godunov” by M. Mussorgsky and “Second-hand Time” by S. Nevsky. The research considered the intonation-genre specificity and its indicators from the point of view of the associative musical text theory. The associative text of “Boris” exists in two versions: as a quotation (in S. Nevsky’s opera “Second-hand Time” was adapted the material from “Boris Godunov” by M. Mussorgsky); b) in the form of a whole work presented by Mussorgsky’s opera “Boris Godunov” in the framework of the entire project “Boris” which is a unique opera phenomenon.